The Use Code Switching of Students During Double Degree Program in Eastern Taiwan - Hesti Miranda (Acitya: Journal of Teaching and Education, 2023)
Language is the vital for human in life. Through language, a human can communicate each other. The phenomenon of an individual uses more than one language to deliver means in some words or sentences is called code-switching. Code-switching researches are easy to find, but most of them are implemented in the classroom. It is rare to find research about code-switching about double degree students. The objectives of this study are to discover what languages that students used for code-switching, to find out the students' motivations, and to know students’ attitudes when used code-switching during their double degree program in Taiwan. This study used the descriptive qualitative method to collect and analyzed the data. Purposive sampling is applied. The subjects are master's degree students that stay for about two semesters in Eastern Taiwan. The Interview was adopted from Hossam Ebid (2017) and it was a semi-structured interview. This study found that the languages English and Bahasa Indonesia are the majority languages that students spoke, Sunda, Chinese, and Spanish are used for code-switching for certain people. The motivations to use code-switching are intimacy, strengthen culture, privacy, maintain the language, sharing, communication, the words that cannot be translated, exploring Taiwan language, get a new friend, and building a relationship. The attitude of the students showed positives toward code-switching. It found also that the attitudes of interlocutors when encounter double degree students, such as angry, afraid, lost interest, happy and confused. This result revealed one layer of language phenomena in Indonesia.